The environmental qualities of lowcost housing schemes: A case study of the environment of a typical superblock at Hanover Park, Phillip, Cape, in February, 1973 - Scheid, Klaus P (School of Architecture, Planning and Geomatics, 2018)
All the coloured townships are located in the Cape Flats, between the Southern and Northern suburbs, which are located along the major transportation routes. 11 For a long time the Cape Flats acted as a formidable barrier to urban expansion and its special character was a major determinant in the growth process of metropolitan Cape Town in its formative stages. During most of this period it remained as unalienated Government waste land, being unsuitable for normal farming operations of the time owing to the sandy nature of its topsoil and its thin clothing of vegetation. It was inaccessible to wagon transport in the absence of hard roads. Overgrazing and firewood collection upset the delicate natural ecology. The removal of the Mediterranean-type flora resulted in shifting sands of the true desert.